Supraoptimal nitrogen sidedressing on morpho-agronomic traits of maize - Fagherazzi, Mariana Mendes; Souza, Clovis Arruda; Casa, Ricardo Trezzi; Coelho, Cileide Maria Medeiros (Revista de Ciências Agroveterinárias, 2016)
Nitrogen is the element that has the most influence on grain yield in maize plantations; however, the excess of this nutrient increases the likelihood of lodging. The occurrence of lodging can be prevented by applying a plant growth regulator. In this respect, an experiment was carried out to evaluate the effects of nitrogen sidedressing above the ideal level, associated with the use of trinexapac-ethyl in maize cv. P30R50H. The experiment was conducted under field conditions during the season 2013/2014, in Lages - SC. The experimental design was a randomized block design with four replications, and the treatments consisted of four nitrogen rates and a rate of trinexapac-ethyl applied at all nitrogen rates. Nitrogen rates were equivalent to 1.0, 1.35, 1.70 and 2.0 times the required rate to reach the yield of 12 t ha-1. The N sidedressing rates were equally divided and applied on plants at phenological stages V4, V7 and V9. The trinexapac-ethyl was applied when the plants reached V10 (ten fully developed leaves) at a concentration of 300 g a.i. ha-1. Only the variable length of the leaf opposite the ear increased with increasing the ideal level of nitrogen sidedressing. Lodging, plant height, leaf chlorophyll, grain yield and nitrogen content in the grains were not affected by N sidedressing above the ideal level, associated with the use of trinexapac-ethyl.